The Study of Language Transfer in EFL Students’ Translation Work - Fikri, Nurul (Indonesian Journal Publisher, 2023)
Speakers of several native languages now use English as their common language. However, English learners struggle to understand the language, especially when it differs from their mother tongues. We can draw a connection between the aforementioned statement and how accurate language shift requires a solid understanding of English to understand translation. As a result, the study titled